Novel Insights Into N-Glycan Fucosylation and Core Xylosylation in C. reinhardtii - Oltmanns, Anne; Hoepfner, Lara; Scholz, Martin; Zinzius, Karen; Schulze, Stefan; Hippler, Michael (Frontiers in Plant Science, 2020)
Chlamydomonas reinhardtii (C. reinhardtii) N-glycans carry plant typical β1,2-core xylose, α1,3-fucose residues, as well as plant atypical terminal β1,4-xylose and methylated mannoses. In a recent study, XylT1A was shown to act as core xylosyltransferase, whereby its action was of importance for an inhibition of excessive Man1A dependent trimming. N-Glycans found in a XylT1A/Man1A double mutant carried core xylose residues, suggesting the existence of a second core xylosyltransferase in C. reinhardtii. To further elucidate enzymes important for N-glycosylation, novel single knockdown mutants of candidate genes involved in the N-glycosylation pathway were characterized. In addition, double, triple, and quadruple mutants affecting already known N-glycosylation pathway genes were generated. By characterizing N-glycan compositions of intact N-glycopeptides from these mutant strains by mass spectrometry, a candidate gene encoding for a second putative core xylosyltransferase (XylT1B) was identified. Additionally, the role of a putative fucosyltransferase was revealed. Mutant strains with knockdown of both xylosyltransferases and the fucosyltransferase resulted in the formation of N-glycans with strongly diminished core modifications. Thus, the mutant strains generated will pave the way for further investigations on how single N-glycan core epitopes modulate protein function in C. reinhardtii.